Analysis of Payroll Accounting Information System at PT. Pertamina Training & Consulting Marketing Operation Region V, East Java Region - Pristiwantiyasih; Suhartono, Edy (PT. LITERASI SAINS NUSANTARA, 2024)
In this research, the author employed a qualitative research method. The study was conducted at PT. Pertamina Training & Consulting MOR V (Marketing Operation Region-Five) in East Java as the population, while the samples to be taken include payroll procedures, overtime calculations, and other supporting documents related to the payroll accounting information system at PT. Pertamina Training & Consulting Marketing Operation Region V in East Java, specifically in the Security Business Services division. Data collection techniques used by the author include passive participatory observation, structured interviews, and documentation. The data analysis technique utilized by the author is descriptive qualitative analysis, examining and evaluating the payroll accounting information system and procedures at PT. Pertamina Training & Consulting Marketing Operation Region V in East Java, Security Business Services division. Based on the research findings and discussions regarding the payroll accounting information system at PT. Pertamina Training & Consulting in East Java, it can be concluded that the payroll information system processes are functioning quite well as they are in accordance with the theory. However, there are several theories not applied in the payroll system at PT. Pertamina Training & Consulting, such as the recording of work hours and time cards, which are commonly used in manufacturing companies. Another example of theory not applied in the payroll system at PT. Pertamina Training & Consulting is the use of pay envelopes, as the salary payments are processed through bank services for transfer to each employee's account.